Mobile commerce opportunities, applications, and technologies of wireless business - May, Paul 1963- (Breakthroughs in application development, 2001)
This book provides the context, architectures, case studies, and intelligent analysis that will help you grasp this rapidly evolving subject. With keen insight into the needs of both camps, May explains the technological aspects of mobile commerce to business decision makers and the business models to the technologists who design and build these electronic systems. It is the one book all relevant parties in a company can read to ensure common understanding. Topics include devices, technologies, applications, standards, security, and more